Structural variations in (001)-oriented layered lead halide perovskites, templated by 1, 2, 4-triazolium. Issue 47 (17th November 2020) - Guo, Yuan-Yuan; Yang, Lin-Jie; McNulty, Jason A.; Slawin, Alexandra M. Z.; Lightfoot, Philip
Abstract : Three new layered hybrid perovskites are reported. (TzH)2 PbCl4 undergoes a unique structural phase transition, due to 'rippling' of perovskite-like layers. Abstract : A new hybrid lead(ii ) halide perovskite, (TzH)2 PbCl4, ([TzH + ] = 1, 2, 4-triazolium), adopts a (001)-oriented layered perovskite structure, which can be considered as derived from the n = 1 Ruddlesden–Popper (RP) type. Variable temperature single crystal X-ray diffraction reveals a structural phase transition in the region 125 K < T < 173 K between a high temperature, high symmetry polymorph, space group Cmcm, and a low temperature, low symmetry chiral polymorph, space group P 21 21 21, which has a tripled unit cell volume. UV-Vis spectra suggest a band gap of 3.30 eV for (TzH)2 PbCl4 . A second polymorph of the bromide analogue, (TzH)2 PbBr4 -II, is also reported, and structural relationships between all three variants are discussed.